Issues of Speech Culture in Navoi's Work - Bakhadirova, Dildora Azodovna (Journal of Higher Education and Academic Advancement, 2024)
In this article, Navai realized that language is a growing and developing necessity that meets the needs of the society. In the work "Muhokamatul-lughatayn" the Arabic language is glorified as a "divine word" and the Persian and Turkish languages are compared.